Nutritional Status and Physical Activity of Elementary Students in Bandung during the Covid-19 Pandemic - Willy Yashilva; Muchamad Rizki Sentani (Journal of Applied Food and Nutrition, 2022)
Introduction: During this Covid-19 pandemic, Exercising and doing physical activity is very necessary to keep the body in shape, but students tend to do a lot of sedentary behavior because they required to stay at home. Sedentary behavior and student health are interrelated because a dangerous sedentary lifestyle increases many diseases and deaths. This study aims to identify nutritional status and physical activity of elementary students in Bandung during the Covid-19 pandemic.Methods: This study using corelational analytic with cross-sectional design. The data collection tools on this research using quisioner that divided into 2 parts. Subject research choosing based on inclusion criteria on this research are student that registered in dapodik data when the research was conducted, no suffer from chronic and congenital disease, and surely provide to be a respondent.Results: The result of the variety analytics showed nutritional status of school-aged children and 84,2 % has normal body mass index and 72,6% has normal height. Based on table 3, 49 of student do sedentary activity and 46 do moderate, 43 of student  do physical activity during sport session about one time, and 2 of them not doing it at all, 50 of student sitting on their spare time, 48 of student sittting on their school break, 43 of student do physical activity after school about 2-3 times, 62 student do physical activity in afternoon about 1-3 times, 39 of student do physical activity on weekends about one times, and their parent's perception about physical activity was 1-2 times do physical activity on spare time.Conclusion: Most children have normal nutritional status, although most children behave sedentary. The results of this study are expected to be an awareness for parents and teachers to encourage children to do more physical activity because hildren who move a lot can avoid obesity and are more fit, especially during this Covid-19 pandemic..